Rancangan Implementasi Sistem ERP (Enterprise Resource Planning) Menggunakan Software Odoo pada CV Nur Rahmat Teknik - Amin Ariq Adiyatama; Otong Rukmana; Ahmad Arif Nurrahman (UNISBA Press, 2023)
Abstract. CV Nur Rahmat Teknik is an MSME (Micro, Small and Medium Enterprises) company that produces heater products in Bandung. The system applied to the company is a conventional system, both in selling electrical equipment and selling the company's heater products. The drawback of the system currently used is that there is no list and number of electrical equipment sold at the company's kiosk, so it takes time to check the equipment. Then the consumer/customer product design order documents are not stored properly which results in the time it takes to find product design order documents at the company or even documents can be lost. Then it is difficult to monitor the company owner, production employees, and kiosk employees regarding the amount of electrical equipment and raw material supplies that are not clearly visible, resulting in a delay in the production process because it takes time to buy and retrieve raw materials from vendors. So we need a database so that data on electrical equipment, raw material supplies, and product designs can be stored properly. An ERP (Enterprise Resource Planning) system is needed to integrate every part of the company. The FAST (Framework for Application of Systems Thinking) method is a system development method used to design information systems through a sequential process [1]. The results of the ERP system implementation design were carried out using Odoo software with the modules used being the Sales, Accounting, Inventory, Manufacturing, Website, Purchase, Point Of Sales, Document, and Live Chat modules. Keywords: ERP (Enterprise Resource Planning), FAST (Framework for Application of Systems Thinking) method, Odoo Software. Abstrak. CV Nur Rahmat Teknik merupakan perusahaan UMKM (Usaha Mikro Kecil dan Menengah) yang memproduksi produk heater di Bandung. Sistem yang diterapkan pada perusahaan adalah sistem konvensional, baik dalam penjualan peralatan listrik maupun penjualan produk heater perusahaan. Kekurangan dari sistem yang digunakan saat ini adalah tidak adanya daftar serta jumlah dari peralatan listrik yang dijual pada kios perusahaan, sehingga diperlukan waktu dalam melakukan pengecekan peralatan. Kemudian pada dokumen-dokumen pemesanan desain produk konsumen/pelanggan tidak tersimpan dengan baik yang mengakibatkan diperlukan waktu untuk mencari dokumen pemesanan desain produk pada perusahaan atau bahkan dokumen dapat hilang. Kemudian sulitnya monitoring dari pemilik perusahaan, karyawan bagian produksi, dan karyawan kios terhadap jumlah peralatan listrik dan persediaan bahan baku yang tidak terlihat secara jelas sehingga mengakibatkan proses produksi terhambat karena diperlukannya waktu untuk membeli dan mengambil bahan baku pada vendor. Sehingga diperlukannya database agar data-data peralatan listrik, persediaan bahan baku, dan desain produk dapat tersimpan dengan baik. Sistem ERP (Enterprise Resource Planning) diperlukan untuk mengintegrasikan setiap bagian pada perusahaan. Metode FAST (Framework for Application of Systems Thinking) merupakan metode pengembangan sistem yang digunakan untuk merancang sistem informasi melalui proses yang berurutan [1]. Hasil rancangan implementasi sistem ERP dilakukan dengan menggunakan software Odoo dengan modul-modul yang digunakan adalah modul Sales, Accounting, Inventory, Manufacturing, Website, Purchase, Point Of Sales, Document, dan Live Chat. Kata Kunci: ERP (Enterprise Resource Planning), metode FAST (Framework for Application of Systems Thinking), Software Odoo.